First Report of Two Unreported Fungi Clonostachys eriocamporesii and Sporothrix euskadiensis Isolated from Soil in Korea - Mohammad Hamizan Azmi; Seong-Keun Lim; Ye-Seo Lee; Jun-Woo Choi; Min-Gyu Kim; SeungYeol Lee; Hee-Young Jung (한국균학회지)
During an exploration of fungal diversity in Korean soil, this study isolated and identified two unrecorded fungal strains, designated KNU-HP-1804 and KNUF-20-007. Morphological and cultural features were examined for initial classification. Cultural and morphological characteristics of strains KNU-HP-1804 and KNUF-20-007 were matched with Clonostachys eriocamporesii CBS 647.91 and Sporothrix euskadiensis CBS 122138T, respectively. To further pinpoint their identity and evolutionary relationships, molecular phylogenetic analyses were conducted using the internal transcribed spacer (ITS) region, translation elongation factor 1-alpha (TEF1), beta-tubulin (TUB2), and calmodulin (CAL). The neighbor-joining (NJ) phylogenetic tree using the concatenated sequences, and the cultural and morphological observations revealed KNU-HP-1804 as C. eriocamporesii, while KNUF-20-007 was identified as S. euskadiensis. To the best of our knowledge, this is the first report on C. eriocamporesii and S. euskadiensis in Korea.